(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
This study was conducted to monitor the present condition of endangered fishes and productivity of Teesta river closest to Teesta barrage situated in the Lalmonirhat district of Bangladesh. Water and sediment samples were collected twice in a month during the study period from six different (3 upstream and 3 downstream) sites with three replications for each. Required information about threatened fishes was collected from the sampling region associated fishermen and fish markets. The study disclosed over 50 threatened fish species in Teesta river including several threatened fishes namely Bagarius bagarius, Sisor rabdophorus etc. The commonly available endangered fishes were Macrognathus aculiatus, Mastacembelus armatus, Barilius tileo, Raiamas bola, Botia dario, B. lohachata etc. which are rarely available in nationwide. Planktonic flora and fauna determination revealed that comparatively higher density of plankton (n >11500 per liter) as well as more number of planktonic flora (>21 nos.) and fauna (>9 nos.) were monitored in the early monsoon and monsoon season (April-September) and comparatively lower planktonic density (n<10000 per liter) and less number were found in premonsoon season (January-February). The investigation of benthic fauna showed that the riverine ecosystem near to barrage contained 16 species of macro-benthos from different groups. Lastly, it can be noticed that it is very essential to take all effective necessary actions to provide good productivity and conserve the ichthyo diversity of Teesta river that will help to conserve the commonly available endangered and critically endangered fishes of Teesta river. Res. Agric., Livest. Fish.7(3): 577-589, December 2020